2021
DOI: 10.52403/ijrr.20210704
|View full text |Cite
|
Sign up to set email alerts
|

The Differences of Myelosuppression before and after Doxorubicin Chemotherapy in Breast Cancer Patients in Rsup. H. Adam Malik Medan

Abstract: Introduction: Breast cancer is formed from breast cells, either lobule or duct epithelium, which undergoes uncontrolled growth and development. The therapy of breast cancer to reduce mortality and morbidity can be done by way of surgery, chemotherapy, and radiotherapy. Doxorubicin chemotherapy is a therapeutic option to kill cells directly or by stopping the cell division based on the tumor pathogenesis. Method: This research is a paired numerical comparative analytical study using a retrospective cohort appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The main targets of destructive free radicals induced by anthracyclines are cell membranes, which are composed of lipids and susceptible to oxidation. 20,21 Elevation of CK-MB and LDH levels in circulation was one of the characteristics of cardiotoxicity. It indicated the occurrence of damage or injury in cardiac cells due to excessive production of free radicals and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…The main targets of destructive free radicals induced by anthracyclines are cell membranes, which are composed of lipids and susceptible to oxidation. 20,21 Elevation of CK-MB and LDH levels in circulation was one of the characteristics of cardiotoxicity. It indicated the occurrence of damage or injury in cardiac cells due to excessive production of free radicals and lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Anthracycline-based regimen therapy is still the standard first-line regimen for breast cancer (Jasra S and Anampa J., 2018). Cytotoxic drugs that can be used alone or in combination as chemotherapy for breast cancer include doxorubicin, cyclophosphamide, paclitaxel, docetaxel, and vincristine (Fernando A, et al ., 2021).…”
Section: Introductionsmentioning
confidence: 99%
“…New findings on ROS have shown that drugs with a ROS mechanism are used to treat cancer because they accelerate tumor cell death. High levels of ROS induce not only tumor cell death but also oxidative damage to normal cells, especially haemopoietic cells in the bone marrow, leading to bone marrow suppression and other adverse effects (Fernando, 2021).…”
Section: Introductionsmentioning
confidence: 99%